The multicultural competence of entry-level housing professionals in the upper Midwest - Cook, Kevin Marcus (Kansas State University, 2016)
In this study, I sought to determine how the multicultural competence scores of entry-level housing professionals were impacted by the demographic characteristics of race, gender, sexual orientation, years of experience, and graduate school diversity curricular content and experiences. Additionally, it was important to establish a baseline of knowledge related to multicultural competence for this particular population of entry-level housing professionals. I selected participants for this study from the 2016 membership directory of the Upper Midwest Region of the Association of College and University Housing Officers (UMR-ACUHO). I used quantitative data analysis methods to answer four research questions. I analyzed the first research question using ANOVA and post hoc tests for each of the demographic variables of race, gender, and sexual orientation. I found statistically significant differences in multicultural competence scores based on race and sexual orientation, while I found no differences by gender. The post hoc examinations revealed that for the various racial categories, there were no statistically significant differences by group. With regard to sexual orientation, I found that gay male participants had multicultural competence scores that were statistically significantly higher than their heterosexual/straight colleagues. I analyzed the third research question using linear regression in an attempt to determine if there was a relationship between years of experience and multicultural competence scores. There was no statistically significant relationship. The final two research questions used ANOVA and post hoc analyses to determine if there were differences in the multicultural competence scores of participants based on the diversity content in their graduate programs and their most impactful multicultural graduate school experiences. I found no statistical differences for either of those research questions.
Keywords: Multicultural Competence; Student Affairs; College housing; University housing; Housing professional; Upper Midwest